Vojtov V.A., Коzyr A.G. Simulation of transient processes in the tribosystem. Part 1. Criteria for evaluation transient processes. - Войтов, В.А.; Козырь, А.Г. (Problems of Tribology, 2014)
The paper presents the theoretical and experimental studies to validate a method of modeling of transients in tribosystem and evaluation criteria of such processes. Criteria for evaluation were obtained in the form of coefficients of the differential equations which describe transient process. It is shown that the proposed coefficients have definite physical meaning and the response of tribosystem on input disturbance (change in load, sliding velocity, etc.).